2008
DOI: 10.1097/01.htr.0000341433.67251.01
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives on Recovery and Social Reintegration After Pediatric Traumatic Brain Injury

Abstract: The present findings support the concurrent validity of parental perspectives of a child's overall recovery and social reintegration after pediatric TBI. Incorporating these views may assist in the rehabilitation of children following brain injury. Parental reasons for judging a child's recovery as "incomplete" may differ as a function of severity of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In this brief time, families are also exposed to decision making regarding their child’s reintegration into their family and community while watching for, or treating, symptoms associated with mild TBI, such as headaches, sleep disturbance, depression, and behavior change (McCabe et al, 2007; Prigatano & Gray, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In this brief time, families are also exposed to decision making regarding their child’s reintegration into their family and community while watching for, or treating, symptoms associated with mild TBI, such as headaches, sleep disturbance, depression, and behavior change (McCabe et al, 2007; Prigatano & Gray, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The model has three main components-brain development and integrity, internal/ external factors, and current cognitive functions-with each having a role to play in the development of social skills. This model is relevant to research investigating the predictors of social outcomes, where a number of cognitive, 21-30 psychological, 31 developmental, 32,33 pre-injury, [34][35][36] and injury factors 7,37 have been investigated, even though few studies have looked across these domains simultaneously. A handful of recent studies have extended this area by exploring the role of environment for social and behavioral outcomes, with findings identifying a role for both distal (e.g., socio-economic status, parent education, and income) and proximal factors (e.g., family functioning and family mental health).…”
Section: Predictors Of Social and Behavioral Outcomesmentioning
confidence: 98%
“…Previous studies have observed novel psychiatric disorders (NPDs) occurring in 10%-100% of children and adolescents with TBI of various severities, including personality changes, attention-deficit hyperactivity disorder (ADHD), behavioral disorders, depression, and anxiety disorders. 4,21,22,[26][27][28]30,31,[33][34][35][36]49 Children and adolescents with psychiatric disorders are at risk for additional long-term comorbidities such as impaired school performance, 9 social isolation, 48 family dysfunction, 55 substance abuse, 45 and suicidal behavior. 19 Successful management of isolated pediatric mood disorders requires a multidisciplinary approach that includes behavioral and pharmacological treatment options.…”
mentioning
confidence: 99%